Don’t Lose Your Brain at Work – The Role of Recurrent Novelty at Work in Cognitive and Brain Aging - Oltmanns, Jan; Godde, Ben; Winneke, Axel H.; Richter, Götz; Niemann, Claudia; Voelcker-Rehage, Claudia; Schömann, Klaus; Staudinger, Ursula M. (Frontiers in Psychology, 2017)
Cognitive and brain aging is strongly influenced by everyday settings such as work demands. Long-term exposure to low job complexity, for instance, has detrimental effects on cognitive functioning and regional gray matter volume. Brain and cognition, however, are also characterized by plasticity. We postulate that the experience of novelty (at work) is one important trigger of plasticity. We investigated the cumulative effect of recurrent exposure to work-task changes (WTC) at low levels of job complexity on gray matter volume and cognitive functioning of middle-aged production workers across a time window of 17 years. In a case-control study, we found that amount of WTC was associated with better processing speed and working memory as well as with more gray matter volume in brain regions that have been associated with learning and that show pronounced age-related decline. Recurrent novelty at work may serve as an ‘in vivo’ intervention that helps counteracting debilitating long-term effects of low job complexity.